Builders! Speed is Vital, Minutes Saved-Lives Saved-poster (London)
1945 1939-1945 "Builders! Speed is Vital, Minutes Saved-Lives Saved-poster" [HFR0012], c. 1940 Ministry of Works poster c.1940 showing a crane driver aimed at workers in the building industry.